HR Professional Role Tensions: Perceptions and Responses of the Top Management Team. Issue 1 (30th December 2013) - Sheehan, Cathy; De Cieri, Helen; Greenwood, Michelle; Van Buren, Harry J.
Abstract The aims of the research are to explore evidence of professional human resource management (HRM) role tensions, the factors that affect HRM role tension, and to consider the impact on management perceptions when role tensions exist. Using a qualitative approach, 25 interviews were conducted in Australia with senior HRM personnel, top management team (TMT) executives, and a management consultant. Findings reveal that the failure of the HRM profession to attract people with a business focus increases HRM role tensions. Respondents report that tensions were reduced when aspects of the HRM role were devolved or outsourced, there was an acceptance of a changed psychological contract, and clearer attempts were made to communicate an agreed‐upon strategic focus for HRM. HRM role bias led to a reduced willingness among TMT members to respect, and communicate with, HRM professionals. The implications of the negative outcomes of HR role tensions are discussed with reference to the power of the HRM function. © 2013 Wiley Periodicals, Inc.